Wire EDM Parameters for Surface Roughness in Straight Gear Manufacturing: An Experimental Study - Amit Hazari; Samsul Mondal; Rajibul Sekh; Aziz Md SK; Purnendu Singha; Rajesh Biswas (International Journal of Engineering and Management Research, 2021)
The gears are an essential component of any system. A gear is a spinning circular machine part with cut teeth, or inserted teeth (called cogs) in the case of a cogwheel or gearwheel, which mesh with another toothed part to convey torque. A gear is sometimes referred as a cog colloquially. Geared devices can adjust a power source's speed, torque, and direction. To eliminate backlash, high precision is required while making gears. Wire cut EDM is a high-precision machining technology that may manufacture high-precision straight gear. The goal of this research is to use the WEDM Process on an EMS 45 to determine the surface roughness of the workpiece and to optimise the influence of current and wire speed on the surface roughness of the straight gear. Wire cut machining parameters employed were 4, 6, and 8 amperes of current and 9, 11, and 13 mm/min of wire speed. Wire has a diameter of 0.25 mm, and the cutting material is brass. It has been demonstrated that as current and wire speed increase, surface roughness decreases, and vice versa. As a result, reduced machine settings can be used to generate a smoother and better workpiece surface.